A New Species of the Genus Duvalius (Coleoptera, Carabidae, Trechini) from Kazakhstan - Belousov, I.A.; Kabak, I.I. (Вестник зоологии, 1999)
Duvalius putshkovi sp. n. is described from Kazakhstan (Western Tien-Shan, Ugam mountain ridge). The species belongs to the same species group as the most other representatives of the genus Duvalius Delar. from Middle Asia and is very closely related to Duvalius alexeevi Belousov, 1991 from Sary-Tshclek Reservcry (western Tien-Shan, Chatkal mountain ridge).